3D Fabrication of Fully Iron Magnetic Microrobots. Issue 16 (4th March 2019) - Alcântara, Carlos C. J.; Kim, Sangwon; Lee, Sunkey; Jang, Bumjin; Thakolkaran, Prakash; Kim, Jin‐Young; Choi, Hongsoo; Nelson, Bradley J.; Pané, Salvador
Abstract: Biocompatibility and high responsiveness to magnetic fields are fundamental requisites to translate magnetic small‐scale robots into clinical applications. The magnetic element iron exhibits the highest saturation magnetization and magnetic susceptibility while exhibiting excellent biocompatibility characteristics. Here, a process to reliably fabricate iron microrobots by means of template‐assisted electrodeposition in 3D‐printed micromolds is presented. The 3D molds are fabricated using a modified two‐photon absorption configuration, which overcomes previous limitations such as the use of transparent substrates, low writing speeds, and limited depth of field. By optimizing the geometrical parameters of the 3D molds, metallic structures with complex features can be fabricated. Fe microrollers and microswimmers are realized that demonstrate motion at ≈20 body lengths per second, perform 3D motion in viscous environments, and overcome higher flow velocities than those of "conventional 3D printed helical microswimmers." The cytotoxicity of these microrobots is assessed by culturing them with human colorectal cancer (HCT116) cells for four days, demonstrating their good biocompatibility characteristics. Finally, preliminary results regarding the degradation of iron structures in simulated gastric acid liquid are provided. Abstract : Biocompatible and degradable Fe microrobots with enhanced magnetic volume are fabricated by 3D template‐assisted deposition. Microhelices are able to execute 3D motion in viscous fluids and outperform metal‐coated polymer structures in upstream motion measurements inside microfluidic channels. Furthermore, microrollers are able to move at 500 µm s −1, about 20 body lengths per second, under low intensity magnetic fields.